45.5k views
4 votes
Simplify x^0yz^-3. Please explain

1 Answer

6 votes

Answer:
(y)/(z^3)

Explanation:

To simplify the expression given in the problem, you must apply the proccedure shown below:

1- According the Exponents Rules, you know the following:


a^0=1\\\\a^(-n)=(1)/(a^n)

2- Therefore, keeping the above on mind, you can simplify the expression given in the problem as you can see below:


x^0yz^(-3)=(1)yz^(-3)\\\\=yz^(-3)\\\\=y(1)/(z^3)\\\\=(y)/(z^3)

User Philip  Dernovoy
by
6.6k points